THE USE OF THE RASCH MODEL IN ANALYSING THE VALIDITY AND RELIABILITY OF STUDENTS’ COPING STRATEGY SCALE - Oktaviani, Maya; Hasanah, Uswatun; Faesal, Muhammad; Elmanora; Zulfa, Vania (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2021)
This research is part of the standardization of the Students' Coping Strategy Scale (SCSS). This study aims to reveal the content validity, empirical validity, and reliability of the SCSS. The non-test instrument consisting of 42 statements from three dimensions: problem-focused coping, emotion-focused coping, and seeking social support. Content validity analysis was carried out by experts to obtain Gregory's content validity coefficient, while the empirical validity and reliability analysis by empirically testing the instrument on 211 respondents and analyzed using the Rasch model approach. The results show that Gregory's content validity coefficient is 0.714, so it needs improvement on some items that are considered unsuitable. Empirical validity analysis using WINSTEPS software shows that three items do not fit the model. The reliability coefficient of the SCSS is 0.99. Thus, the remaining 39 items are appropriate to be used to measure students' coping strategies.